2009
DOI: 10.1111/j.1600-0854.2009.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Dynamics in Cultured Mammalian Cells

Abstract: Despite the identification and characterization of various proteins that are essential for peroxisome biogenesis, the origin and the turnover of peroxisomes are still unresolved critical issues. In this study, we used the HaloTag technology as a new approach to examine peroxisome dynamics in cultured mammalian cells. This technology is based on the formation of a covalent bond between the HaloTag protein-a mutated bacterial dehalogenase which is fused to the protein of interest-and a synthetic haloalkane ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
125
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(134 citation statements)
references
References 51 publications
6
125
2
1
Order By: Relevance
“…In these cells, exosome release was slightly reduced. However, we have to consider that the levels of this enzyme were only depleted by ϳ70%, probably due to the long half-life of peroxisomes and of this enzyme (50,51). The release of exosomes is the end point of a process that can be divided into several steps.…”
Section: Discussionmentioning
confidence: 99%
“…In these cells, exosome release was slightly reduced. However, we have to consider that the levels of this enzyme were only depleted by ϳ70%, probably due to the long half-life of peroxisomes and of this enzyme (50,51). The release of exosomes is the end point of a process that can be divided into several steps.…”
Section: Discussionmentioning
confidence: 99%
“…This constant turnover is essential for preservation of cellular and organellar competence. Experimental studies demonstrated that peroxisomes have a half-life of circa 48 h under basal conditions and are primarily degraded by autophagy (44). Autophagy is a highly conserved lysosome-dependent pathway that maintains the quality of cellular components through continual removal of redundant or damaged proteins or entire organelles (72).…”
Section: Peroxisomal Homeostasis and Autophagymentioning
confidence: 99%
“…Accordingly, the peroxisomal compartment adapts to changes in cellular microenvironments through proliferation and specific degradation (Fagarasanu et al, 2007;Oku and Sakai, 2010). Studies on peroxisome turnover in mammalian cells revealed a half-life of about two days (de Duve et al, 1974;Huybrechts et al, 2009). To guarantee the maintenance of peroxisomes under varying conditions, mechanisms exist that insure their steadystate either by growth and division of pre-existing organelles or via de novo biogenesis from the endoplasmic reticulum (Geuze et al, 2003;Motley and Hettema, 2007;Toro et al, 2007;Toro et al, 2009).…”
Section: Introductionmentioning
confidence: 99%